2014
DOI: 10.1111/jep.12200
|View full text |Cite
|
Sign up to set email alerts
|

Does the CONSORT checklist for abstracts improve the quality of reports of randomized controlled trials on clinical pathways?

Abstract: The reporting quality of abstracts of RCTs on clinical pathway still should be improved. After the publication of CONSORT for abstracts guideline, the RCT abstracts reporting quality were improvement to some extent. The abstracts in Chinese journals showed non-adherence to the CONSORT for abstracts guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 15 publications
4
24
0
1
Order By: Relevance
“…In addition, less than 5% of the abstracts provided sufficient information for participants, outcome in the methods section, randomization, and trial registration. This pattern of inadequate reporting is generally in line with findings of several previous studies in dentistry [9,13,14] and other specialties [15][16][17], and indicates a lack of awareness of the CONSORT for Abstracts guidelines among researchers in the filed of laser medicine.…”
Section: Overall Reporting Qualitysupporting
confidence: 87%
“…In addition, less than 5% of the abstracts provided sufficient information for participants, outcome in the methods section, randomization, and trial registration. This pattern of inadequate reporting is generally in line with findings of several previous studies in dentistry [9,13,14] and other specialties [15][16][17], and indicates a lack of awareness of the CONSORT for Abstracts guidelines among researchers in the filed of laser medicine.…”
Section: Overall Reporting Qualitysupporting
confidence: 87%
“…This guideline was not designed to be used to assess the risk of bias in RCTs, rather to improve the reporting of RCTs. Based on assessments using these guidelines, the reporting of abstracts has been characterized as suboptimal (Klassen et al, 2002;Can et al, 2011;Ghimire et al, 2012;Cui et al, 2014;Shin et al, 2015). A potential reason for this, even after the development of the CONSORT for Abstracts checklist, is the low uptake of the checklist by relevant stakeholders, including authors and journal editors (Cui et al, 2014;Shin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Based on assessments using these guidelines, the reporting of abstracts has been characterized as suboptimal (Klassen et al, 2002;Can et al, 2011;Ghimire et al, 2012;Cui et al, 2014;Shin et al, 2015). A potential reason for this, even after the development of the CONSORT for Abstracts checklist, is the low uptake of the checklist by relevant stakeholders, including authors and journal editors (Cui et al, 2014;Shin et al, 2015). A 2014 systematic review of abstracts of papers published describing RCTs in the top-tier general medicine journals indicated that while there was a considerable improvement in the quality of reporting from 2007 to 2012, some items still remain poorly reported (Mbuagbaw et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, attempts have been made by researchers to evaluate the completeness of articles and adherence to reporting guidelines among different medical specialties and biomedicine. Most come to the conclusion, that either the use of RGs is insufficiently required by publishing journals, or that the implementation of RGs in final articles is unsatisfactory …”
Section: Introductionmentioning
confidence: 99%